Consumption of Yogurt Containing Probiotic Bifidobacterium Lactis Reduces Streptococcus mutans in Orthodontic Patients - Armelia Sari Widyarman; Shirley Trisna Yunita; Tjokro Prasetyadi (Scientific Dental Journal, 2018)
Background: Probiotic bacteria is commonly used as a food supplement intended to benefit the host by improving intestinal bacterial balance. Probiotics have also been investigated from the perspective of oral health. Objectives: The purpose of this study was to investigate the effect of daily intake of yogurt containing probiotic Bifidobacterium animalis subsp. lactis BB-12 (B. lactis) on salivary Streptococcus mutans (S. mutans) counts in patients undergoing fixed orthodontic treatment. Methods: Saliva samples were collected from each subject (n = 7; mean age, 21 years) using spitting method in centrifuge tubes at baseline and two weeks after daily probiotic yogurt consumption. B. lactis BB-12 and S. mutans ATCC 25175 were cultured in BHI-broth (37ºC, anaerobic conditions). After 48 hours incubation, the number of colonies on each dilution plate was used to extrapolate a standard curve. The total number of target DNA molecules were identified using Real-Time PCR followed by SYBR Green reagents and 16S rRNA gene specific primers S. mutans and B. lactis BB-12. Data were analyzed statistically using paired-sample t-tests. Results: Statistical evaluation indicated that there was a significant reduction in the presence of S. mutans before probiotic yogurt consumption, (4.73 ± 1.43) log10 CFU/mL and after two weeks of daily consumption of probiotic yogurt, (4.03 ± 0.77) log10 CFU/mL, p = 0.001. Moreover, no B. lactis was found in the saliva of any of the subjects before probiotic consumption, but after two weeks of consumption, B. lactis was found in the saliva of four subjects. Conclusions: Consuming probiotic yogurt containing B. lactis reduced the quantity of S. mutans in the saliva of subjects during fixed orthodontic treatment. Thus, the probiotic bacteria could be beneficial in improving oral health.